ENTREPRENEURSHIP AND SOCIAL NEEDS AND OPPORTUNITIES (Annual of the Faculty of Philosophy in Skopje, 2015)
The issues of social entrepreneurship and its impact, and the possibilities of expression and institutional shaping and support can be analyzed and reviewed from numerous different aspects of the phenomenon. In literature and in the practices of many countries are perceived organizational forms that with systemic regulation are affecting more or less expression of social entrepreneurship. The possibilities that exist are analyzed to strengthen this form of engagement and expression because of given positive impacts on employment that are observed in many countries.As a general question that is imposed is how to regulate the field of social entrepreneurship within the legal and economic system of a country. It is necessary the recognition of social entrepreneurship, the importance and the role it has, especially in the social sphere and employment opportunities for the categories of persons that the labor market does not accept or recognize. Social entrepreneurship differently is expressed and properly shaped within the institutions and the systems and it is important to support for its full expression.
Keywords: SOCIAL ENTREPRENEURSHIP; SIGNIFICANCE; SUPPORT; EMPLOYMENT